Application of Saccharomyces cerevisiae as a biocontrol agent against Fusarium infection of sugar beet plants - Shalaby, Moustafa El-Sayed; El-Nady, Mohamed Fathi (Acta Biologica Szegediensis, 2008)
Applicability of Saccharomyces cerevisiae as a biocontrol agent of Fusarium oxysporum and as plant growth promoter was investigated. At 5 g L-1concentration, germination rate of the soaked seeds reached 85.83% in comparison with 54.00% for the untreated ones. Plant growth parameters, chlorophyll contents, TSS and sucrose percentages were also tested. Application of 5 g L-1 of yeast resulted in a reduction of the pre- and post-emergence damping-off 6.67 and 11.67%, respectively. Survival of treated plants increased to 83.33% in comparison with 30.00% for the pots inoculated with the pathogen containing untreated seeds. Linear growth of F. oxysporum was inhibited with 39.52% and 50% by using 5 g L-1 and 6.35 g L-1 of the yeast, respectively.